Syndrome of inappropriate antidiuretic hormone secretion induced by the phytotherapy Harpagophytum procumbers: case report - Carvalho,Renata Reis (2017)
Abstract Introduction: The syndrome of inappropriate antidiuretic hormone secretion (SIADH) is the inability of antidiuretic hormone (ADH) suppression, compromising the mechanisms of water excretion and urinary concentration. It manifests as hyponatremia and its symptoms, especially neurological. There are many causes that trigger such disease, notably: central nervous system disorders, malignant neoplasm, drugs and others. Case Report: A 65 years female hypertensive patient presented clinical and laboratory manifestations of hyponatremia due to SIADH. It happened twice under use of herbal medication for osteoarthritis treatment. Discussion: The drug-related hyponatremia can be triggered by direct effect of the drug or by association with SIADH. The clinical manifestations presented could have been related to psychiatric condition and may have severe outcome if not properly diagnosed. The association of an herbal medicine to SIADH could be confirmed after a new episode of hyponatremia related to Harpagophytum procumbers reintroduction. Our literature review did not find this herbal medicine associated with SIADH, so far. Conclusion: SIADH may be caused by herbal medicine described from now on their association in the literature.